KAUSALITAS ANTARA EKSPOR DAN PERTUMBUHAN EKONOMI - Aliman Aliman; A. Budi Purnomo (Journal of Indonesian Economy and Business (JIEB), 2001)
The debate about the role of exports in the development of economic theory has emerged since the 1950s. In the macroeconomic theory, the relationships between export and economic growth and / or national income is an identity because export is a part of national income, but in development economics, heavily concern over matters wether export make prosperity (wealth) or suffering to a nation. Jung and Marshall (1985) examine four viewpoints characterize equally plausible hypothesis of relationships between export and economic growth: (1) export-led growth hypothesis, (2) internally generated export hypothesis, (3) export-reducing growth hypothesis and (4) growth-reducing export hypothesis. The empirical result using real national income and real export data over 1969–1997 suggests that error correction causality tests show bidirectional pattern, but according to the value of error correction term, adjustment coefficient reaction, Granger-causality test (1969) and final prediction error (FPE) show unidirectional causality from real national income to real export. Thus, over the period 1969-1997, Indonesia supported internally generated export hypothesis.